Analisis Framing Politik Identitas Pasangan Anies Baswedan - Muhaimin Iskandar dalam Pemberitaan Pilpres 2024 di Media Indonesia - Rifat Farihi, Haikal; Lukmantoro, Triyono; Hasfi, Nurul (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The results of this research reveal that Media Indonesia has framed identity politics in 60 articles within the structure of straight news, specifically in the title, lead, and body of the articles. The titles feature topics related to religion at 58.3% and social groups at 31.7%. Images displayed symbols of SARA with activities comprising 36.7%, objects at 20.0%, symbols at 13.3%, and locations at 5.0%. The diction supporting SARA policies accounted for 13.3%, while identity-related diction reached 76.6%. The highlighting of support from identity figures was noted at 53.3%, and the mention of SARA attributes also stood at 53.3%. In the lead section, diction supporting SARA policies was at 5.0%, while identity related diction surged to 85.0%. The highlighting of support from identity figures was recorded at 55.0%, and the mention of SARA attributes reached 61.7%. In the body of the articles, supporting diction for SARA policies was at 13.3%, while identity-related diction reached 90.0%. Support from identity figures was noted at 53.3%, and SARA attributes were mentioned at 70.0%. The news sources supporting the narrative of identity politics included political leaders at 51.7%, religious figures at 18.3%, and leaders of religious organizations at 16.7%.